2007
DOI: 10.1126/science.1131295
|View full text |Cite
|
Sign up to set email alerts
|

Wandering Minds: The Default Network and Stimulus-Independent Thought

Abstract: Despite evidence pointing to a ubiquitous tendency of human minds to wander, little is known about the neural operations that support this core component of human cognition. Using both thought sampling and brain imaging, the current investigation demonstrated that mind-wandering is associated with activity in a default network of cortical regions that are active when the brain is "at rest." In addition, individuals' reports of the tendency of their minds to wander were correlated with activity in this network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

108
1,827
4
22

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,444 publications
(2,010 citation statements)
references
References 21 publications
108
1,827
4
22
Order By: Relevance
“…In recent years, it has been shown that levels of DMN activation are linked to the frequency and depth of mind‐wandering (Christoff, Gordon, Smallwood, Smith, & Schooler, 2009; Mason et al., 2007; Scheibner et al., 2017; Smallwood & Schooler, 2015). Hereby, mind‐wandering was defined as any kind of cognition independent of the task at hand, involving processes like retrieval of autobiographic memory, future planning or evaluating and judging the present (Scheibner et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, it has been shown that levels of DMN activation are linked to the frequency and depth of mind‐wandering (Christoff, Gordon, Smallwood, Smith, & Schooler, 2009; Mason et al., 2007; Scheibner et al., 2017; Smallwood & Schooler, 2015). Hereby, mind‐wandering was defined as any kind of cognition independent of the task at hand, involving processes like retrieval of autobiographic memory, future planning or evaluating and judging the present (Scheibner et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Brain regions involved in this intrinsic network have been proposed to comprise regions of the so‐called default‐mode network (DMN) containing hubs in the posterior cingulate cortex (PCC)/precuneus, medial prefrontal cortex (MPFC)/ventral anterior cingulate cortex (vACC) and parietal regions. Cognitive processes driven by these regions involve self‐generated thought, autobiographical memory, mind‐wandering, and daydreaming (Lieberman, 2007; Mason et al., 2007; Scheibner, Bogler, Gleich, Haynes, & Bermpohl, 2017; Smallwood & Schooler, 2015). When these brain regions are active, the mind is therefore involved in internally directed thoughts and external tasks might be difficult to perform when initiated unexpectedly.…”
Section: Introductionmentioning
confidence: 99%
“…This is an intrinsically correlated network of brain regions that is regularly observed to deactivate during attentiondemanding cognitive tasks. Activation of this network has recently been linked to stimulus-independent thought, or in other words, mind-wandering (Mason et al, 2007). The presently observed negative correlation of frontal theta power with the DMN therefore suggests that frontal theta activity can be used as an index of DMN activity, at least in the resting state condition.…”
Section: Discussionmentioning
confidence: 85%
“…We have demonstrated [Fingelkurts & Fingelkurts, forthcoming] that these highly stable OMs constitute the set of cortical areas that has been named as the "Default Mode Network" (DMN) [480]. Nowadays researchers tend to associate this DMN either with the stimulus-independent thought, mind-wandering and the internal "narrative" [481,482] or with the "autobiographical" self [481,483], "chronic" self-evaluation [484] being a "self", or having self-consciousness [485][486][487]. Indeed, as we have discussed in Section 3, a subject that experiences phenomenal self-consciousness always feels directly present in the center of an externalized multimodal perceptual reality [72,367].…”
Section: Figure 9 Schematic Illustration Of Operational Modules (Omsmentioning
confidence: 99%